HUBUNGAN PERILAKU HIDUP BERSIH DAN SEHAT TERHADAP KEJADIAN DIARE PADA BAYI USIA 6-12 BULAN DI PMB SRI INDIARTI, S.Keb., Bd SINGOSARI KABUPATEN MALANG - Nuraini, Ayu Eka; Indriarti, Ina; Keswara, Nila Widya (NHM PRESS, 2024)
According to the Extraordinary Events (KLB) of diarrhea in the 2018 Basic Health Research Results, 12.3% of toddlers had diarrhea on average that year. (The Ministry of Health of the Indonesian Republic, 2021). Diarrhea cases were highest in West Java (151,878 cases) and lowest in East Java (Ministry of Health, 2018). The Singosari Community Health Center in Malang Regency reported 1,362 cases of diarrhea in 2014, 2,601 cases in 2015, and 4,904 cases in 2016. In the meantime, PMB Bu Indi, Nampes Batu Retno Hamlet, Singosari District, Malang Regency, reported 80 instances of diarrhea episodes. This study's objectives were to promote clean, healthy living habits and ascertain the frequency of diarrhea episodes in babies aged 6 to 12 months at PMB Sri Indiarti Singosari in Malang Regency. In this study, a correlational research design and cross-sectional technique are used. This study involved 72 participants, with 61 randomly selected from the 72 children (6–12 months) suffering from diarrhea at PMB Sri Indriarti Singosari. The findings indicated that twenty respondents exhibited poor PHBS behavior, forty-one respondents had diarrhea, and twenty respondents did not have diarrhea. The lambda contingency coefficient test revealed a p-value of 0.007 < 0.05, indicating a correlation between diarrhea and clean and healthy living practices in newborns 6 to 12 months old in PMB Sri Indiarti, S.Keb., and Bd Singosari Malang Regency. Health education about clean and healthy living habits is crucial to lowering the incidence of baby diarrhea episodes.